Fast Parallel Molecular Solution to the Hitting-Set Problem - Nung-Yue Shi; Chih-Ping Chu (2008 Eighth International Conference on Intelligent Systems Design and Applications, 2008)
The hitting-set problem is an NP-complete problem in set theory. Assume that we have collection C of subsets of a finite set S, and a positive integer K les |S|, and we would like to know if there is a subset S' sube S with |S'| les K such that S' hits (contains) at least one element from each subset in C. In this paper, the DNA-based algorithm is proposed to solve the hitting-set problem. Furthermore, the simulated experiment is applied to verify correction of the proposed DNA-based algorithm for solving the hitting-set problem.